PELAKSANAAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN DI KECAMATAN MEDANG KAMPAI KOTA DUMAI (STUDI PERBANDINGAN SEBELUM DAN SETELAH DIKELOLA SECARA OTONOM TAHUN 2012-2013) - Desi Anggraini; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study wants to investigate and analyze the implementation of Withholding Tax on Land and Building sector in Rural and Urban In Sub Medang Kampai Dumai (Comparative Study Before And After Management of the Autonomous Year 2012-2013).And the purpose of this study was to determine the implementation of land and building tax collection sector in Rural and Urban District of Medang Kampai Dumai before and after managed autonomously Year 2012-2013 and to know what are the factors that affect not optimal for collection of the Property Tax Sector in Rural and Urban District of Medang Kampai Dumai after managed autonomously .This study uses qualitative research methods to include an assessment of descriptive data . Intake of informants in this study was purposive sampling that data source retrieval techniques with particular consideration , particular consideration is the person who is considered the most out of what we expect or as a ruler that will allow researchers to explore the object / social situation under study .Based on the research that has been done is used the theory of regional autonomy . Researchers concluded Implementation of Tax Collection Earth And Building sector in Rural and Urban District of Kampai Medang Dumai (Comparative Studies Before and After Managed Autonomous Year 2012-2013) have not worked well because it has been a decline in realized PBB - P2 after managed by region. Still there are constraints faced by the City of Dumai are problems associated with the ability of local government officials , taxpayers awareness is still low and Updates Database Systems passive .Keywords: Autonomy, Tax Management of Land and Building Rural and Urban